”The unmanned ground vehicles to be used in future military operations” - Andersson, Christian A. (Tiede ja ase, 2022)
Abstract—Unmanned ground vehicles are fast developing because of advances in other relevant technologies like artificial intelligence and telecommunications. These machines provide new possibilities and liberate both resources and personnel from different tasks. Because of this, the time is ripe for militaries around the world to start developing this type of machines for military use. The militaries have had interest in this technology for decades. However, there are not any recent written articles which would gather and provide information about this type of machines, even though there is plenty of discussion around the development of these types of robots and the morality of their use. Therefore, the purpose of this article is to gather available information and technical data about current models under development for the militaries, as well as provide insight to these machines and their current capabilities and limitations. In addition, the goal is to provide insight on lethal autonomous weapon systems and their ethical morality. This article will also focus only on Unmanned Ground Vehicles which cannot be manned and are meant for combat and/or combat-support. Keywords— Unmanned ground vehicle, Lethal autonomous weapon systems, UGV, LAWS, robot, autonomous, track, wheeled, Uran-9, weapon.